Fragilidade à erosão hidríca no município de Sananduva- RS com base na relação entre declividade, uso e cobertura da terra e processos erosivos - Rodrigues, Ivete (2018)
The geomorphological units contained in the geographic space have fundamental characteristics for anthropic appropriation. The differentiated distribution both in the resident population and in the economic activities developed also occurs by the control exercised due to the physical characteristics of the places. The appropriation of the man in the localities causes that the changes in the landscape occur along the historical time. The marks left by these changes reveal some impacts that, most of the times, are occasioned or accelerated by the anthropic action. The physical characteristics of the places are being modified, factor that makes the environment of these places fragile to the degradation. Historically, with the evolution of techniques mainly in agriculture, the various environments in the geographical space were modified, beginning by the man's need to cultivate his lands, as a way of survival, later to serve the foreign market. The modernization of agriculture on the one hand led to the increase and acceleration of production, but on the other, it degraded natural resources. The alteration in these physical elements caused some negative impacts, among these can be mentioned acceleration of erosive processes. Based on this, the study aims to understand the relationship between slope-slope, land use and spatialisation of erosion processes as a subsidy to the study of water erosion fragility in the municipality of Sananduva, located in the northeast of the state of Rio Grande do Sul, corresponding to the transition area between the Campos Gerais Plateau and Dissected Plateau of the Uruguay River. Through the study of these variables, it is expected to understand and evaluate how the slope and land use parameters influence the distribution of erosive processes and, consequently, the fragility to water erosion. The research was developed from the deductive method, and the methodological approach was based on the systemic analysis of the variables: slope, land use and cover and erosive processes. The research consisted in the mapping of the terrain slope, in the identification of the spatialisation of erosive processes and anthropic factors of land use and land cover. From the mapping of these variables, fragility maps of each of them were elaborated and values that resulted in different fragility scenarios were attributed to water erosion. Among the scenes it was possible to choose a best suited the reality of the study area, for this, the field work was fundamental to choose the scenario closest to reality. The methodology of this research led to the identification of important results: The areas with the highest slope are concentrated in the so-called Dissected Plateau of Uruguay. The areas with the highest rate of occurrence of erosive processes are also found in the Planalto dos Campos Gerais. The land use and cover has the predominance of crops followed by native forest and are distributed according to certain slopes. The fragility of water erosion is also concentrated according to the pattern of declivity, land use and already active erosion processes. Considering the scenarios produced, targets can be drawn for conservation of areas by municipal public agencies.